Differences in the contractile properties of the biceps femoris and semitendinosus muscles throughout a season in professional soccer players - Fernández-Baeza, D.; Diaz-Ureña, G.; González-Millán, C. (Journal of Human Kinetics, 2022)
The aim of this study was to monitor seasonal changes in the mechanical and neuromuscular characteristics of the knee flexor muscles with tensiomyography, the biceps femoris (BF) and semitendinosus (ST) muscles, of 27 soccer players. All male professional soccer players (age 25 ± 4 years) were measured at the beginning of the preseason (second week) and in the competitive season (10 weeks later). The variables contraction time (Tc) and muscle displacement (Dm) showed significant differences in some muscles, and in others they indicated a tendency to change. In general, the BF improved (more explosive and better muscle tone) and the ST worsened (slower and worse muscle tone) its values during the season. The findings of this study suggest that usual daily soccer training and weekly competition might produce antagonistic changes between the knee flexor muscles.